Insight into the diagnosis and management of subclinical genital tuberculosis in women with infertility - Nalini Mahajan; Padmaja Naidu; Simran Deep Kaur (Wolters Kluwer Medknow Publications, 2016)
Genital tuberculosis (GTB) is an important cause of infertility in India. Lack of an accurate diagnostic test has led to an indiscriminate use of antitubercular treatment in infertile women. Apart from concerns of drug toxicity, this may be a contributing factor in the increasing incidence of multidrug-resistant TB reported in India. We conducted a study to analyze whether a combination of tests could help improve diagnostic accuracy. An algorithm for the management of GTB in infertile women based on the use of multiple tests is presented.